ChemInform Abstract: Copper‐Based Metal—Organic Frameworks as Reusable Heterogeneous Catalysts for the One‐Pot Syntheses of Imidazo[1, 2‐a]pyridines. Issue 1 (January 2015) - Puthiaraj, Pillaiyar; Ramu, Andy; Pitchumani, Kasi
Abstract The catalyst can be reused at least 5 times with only a slight decrease in yield.